Desenvolvimento de revestimento com potencial prebiótico e antioxidante e sua aplicação em melão minimamente processado - Silva, Débora Samara Oliveira e (2021)
Edible and biodegradable coatings have been used in the preservation of processed fruits minimally, due to their barrier properties to gas exchange and, at the same time, they can serve as carriers of functional ingredients such as yacon syrup, which has fructooligosaccharides (FOS) and phenolic compounds in its composition potentially beneficial to health. Therefore, this research aims to develop edible coating (film) based on bovine gelatin added with yacon syrup as a functional ingredient, and characterize it as to its functional and antioxidant potential, as well as evaluate its application bioactive packaging in melon processed minimally. Yacon syrup was obtained by microfiltration characterized by physical, chemical and physicochemical analyses. The bovine gelatin films with and without yacon syrup were evaluated by physical, barrier, optical and mechanical properties. Coated and uncoated cantaloupe melons (control) were analyzed for quality, antioxidant potential, tissue structural integrity, microbiological analysis and volatile compounds for seven days at 10 °C. The data from the study were submitted to analysis of variance and Tukey's test at 5% of probability. The results highlight that the syrup is an ingredient with potential for food enrichment, due to its high levels of bioactive, chlorogenic acid, FOS and minerals compounds. The edible film of gelatin with yacon syrup was characterized as a biotechnological product that can exhibit a protective effect, potential for functional application in fresh and/or processed fruits and vegetables. The minimally processed coated melons had high contents of excellent bioactive compounds for the human diet, suitable to consumption for five days.